Liberalism and the Limits of Power - Williams, J. author. aut Link
XII, 176 p.
Keywords: This book provides the first critical assessment of important recent developments in Anglo-American liberal theorizing about limited government. Following a comparative study of canonical liberal philosophers Hayek and Rawls, the book reveals a new direction for conceptualizing limited government in the twenty-first century, highlighting the central role that democratic politics - rather than philosophical principles - should play in determining the uses and limits of state power in a liberal regime. Williams draws on recent scholarship in the field of democratic theory and cultural studies in arguing for a shift in the ways liberals approach the study of politics.